2020
DOI: 10.1038/s41586-020-1971-z
|View full text |Cite
|
Sign up to set email alerts
|

Live-animal imaging of native haematopoietic stem and progenitor cells

Abstract: The biology of hematopoietic stem cells (HSCs) has predominantly been studied under transplantation conditions 1 , 2 . Particularly challenging has been the study of dynamic HSC behaviors given that live animal HSC visualization in the native niche still represents an elusive goal in the field. Here, we describe a dual genetic strategy in mice that restricts reporter labeling to a subset of the most quiescent long-term HSCs (LT-HSCs) and that is compatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
197
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(204 citation statements)
references
References 50 publications
6
197
1
Order By: Relevance
“…Trabecular bone may therefore absorb calcium in steady state in young individuals. Intriguingly in this context, a recent report indicates that HSCs localize near areas of bone turnover, which may affect local calcium concentrations . While a recent report showed expansion of HSCs in vitro , among other measures by replacing albumin with polyvinyl alcohol l , low‐calcium cultures can open avenues for HSC manipulation based on their specific physiological features.…”
Section: Introductionmentioning
confidence: 99%
“…Trabecular bone may therefore absorb calcium in steady state in young individuals. Intriguingly in this context, a recent report indicates that HSCs localize near areas of bone turnover, which may affect local calcium concentrations . While a recent report showed expansion of HSCs in vitro , among other measures by replacing albumin with polyvinyl alcohol l , low‐calcium cultures can open avenues for HSC manipulation based on their specific physiological features.…”
Section: Introductionmentioning
confidence: 99%
“…In the liver of the fetus, or in the bone-marrow of adult, hematopoietic stem and progenitor cells (HSPCs) sense and respond to numerous biochemical stimuli (Pinho and Frenette, 2019). Within the bone-marrow, the vascular network and the bone matrix constitute local niches that impart distinct and specific signals regulating the quiescence, proliferation and differentiation of HSPCs (Morrison and Scadden, 2014) (Christodoulou et al, 2020) (Guezguez et al, 2013). Perturbed interactions between HSPCs and their niches have been associated with blood malignancies and ageing (Verovskaya et al, 2019), underscoring the importance of better understanding how HSPCs sense and respond to stromal and endothelial cells in the bone-marrow (Ceafalan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the similarities and differences between the polarities of migrating and anchored HSPCs are still unclear. Such investigation appear all the more necessary that it has recently been revealed that quiescent longterm hematopoietic stem cells are actually non-motile in vivo (Christodoulou et al, 2020). Although a lot has been learned from co-culture experiments, it has remained technically challenging to study the specific role of cell adhesion independently of cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…This technology offers a new way of viewing the metabolic processes of all cells, independent of their origin, phenotype, or state of differentiation, as respiration is fundamental to every cell type. The technology presented by Okkelman et al may complement two other readouts of nutrition and respiration already employed in intravital imaging: the ubiquitous coenzyme‐dependent (NAD(P)H and FAD) metabolism and oxygen availability . However, the performance of the current technology has not been yet applied intravitally, the results presented by the authors convincingly demonstrate its power and feasibility for use with intravital imaging.…”
mentioning
confidence: 97%
“…However, even with this success, advances that expand the utility of the technique and enable IVM to provide more complete information about in vivo pathophysiological phenomena at the single‐cell level were still necessary and continue to be made . These recent developments include (1) expanding the spectral and spatiotemporal boundaries of the current technology, (2) retrieving more detailed molecular information on cellular and tissue functions within living organisms, and (3) translating basic science knowledge into clinically relevant information . The publications in this special issue, Intravital Microscopy: Innovations and Applications , review these recent achievements, as well as present new advances in the IVM of osteoimmunological cross talk, musculoskeletal development, infection biology, and cancer research.…”
mentioning
confidence: 99%